Racial and ethnic differences in parenting stress: evidence from a statewide sample of new mothers - Nam, Yunju; Wikoff, Nora; Sherraden, Michael (Springer, 2015)
Parenting stress can have long-term effects on parents and children, but little research has been done on racial and ethnic differences. We examine parenting stress among White, Black, American Indian, and Hispanic mothers with infants younger than 9 months old. We use birth certificate data and baseline survey data from the SEED for Oklahoma Kids experiment. The study selected its sample from the birth certificates of all infants born in Oklahoma during a certain time period and oversampled three minority groups using stratified random sampling (N = 2,626). The dependent variable is a parenting stress scale created using four questions about mothers’ feelings and perceptions of parenting responsibilities. We employ ordinary least squares regressions and Blinder–Oaxaca decompositions. On average, mean parenting stress scores among Whites (2.80) and American Indians (2.92) are significantly lower than among Blacks (3.17) and Hispanics (3.44). Regressions indicate that—across all four groups—parenting stress is positively associated with maternal depression and negatively associated with social supports. Decomposition results show that different levels of social supports explain 14 to 30 % of the group differences between Whites and the three minority groups. Different levels of depression score explain a significant portion of the disparity between Whites and Blacks (19 %). If the proportion of native-born mothers among Hispanics were as high as that among Whites, about one-third of the gap in parenting stress would disappear. Findings call for interventions to reduce depression and strengthen social supports for new mothers, especially among racial and ethnic minorities.